Pharmacokinetics and pharmacodynamics of single and multiple doses of the glucagon receptor antagonist LGD‐6972 in healthy subjects and subjects with type 2 diabetes mellitus. Issue 1 (31st August 2016) - Vajda, Eric G.; Logan, Douglas; Lasseter, Kenneth; Armas, Danielle; Plotkin, Diane J.; Pipkin, JD; Li, Yong-Xi; Zhou, Rong; Klein, David; Wei, Xiaoxiong; Dilzer, Stacy; Zhi, Lin; et al.
Abstract : Aim: To evaluate the safety, tolerability, pharmacokinetics and pharmacodynamics of single and multiple doses of a novel, oral glucagon receptor antagonist, LGD‐6972, in healthy subjects and subjects with type 2 diabetes (T2DM). Methods: In the single ascending dose study, LGD‐6972 (2‐480 mg) was administered to healthy subjects (n = 48) and T2DM subjects (n = 8). In the multiple ascending dose study, healthy subjects (n = 12) received a dose of 15 mg LGD‐6972 and T2DM subjects (n = 36) received doses of 5, 10 or 15 mg of LGD‐6972 daily for 14 days. Results: LGD‐6972 had linear plasma pharmacokinetics consistent with once‐daily dosing that was comparable in healthy and T2DM subjects. Dose‐dependent decreases in fasting plasma glucose were observed in all groups with a maximum of 3.15 mmol/L (56.8 mg/dL) on day 14 in T2DM subjects. LGD‐6972 also reduced plasma glucose in the postprandial state. Dose‐dependent increases in fasting plasma glucagon were observed, but glucagon levels decreased and insulin levels increased after an oral glucose load in T2DM subjects. LGD‐6972 was well tolerated at the doses tested without dose‐related or clinically meaningful changes in clinical laboratory parameters. No subject experienced hypoglycaemia. Conclusion: Inhibition of glucagon action by LGD‐6972 was associated with decreases in glucose in both healthy and T2DM subjects, the magnitude of which was sufficient to predict improvement in glycaemic control with longer treatment duration in T2DM patients. The safety and pharmacological profile of LGD‐6972 after 14 days of dosing supports continued clinical development.